Description of tetragonal pore space structure of porous materials - Cieszko, M.; Kriese, W. (Archives of Mechanics, 2006)
The generalized macroscopic description is formulated in the paper for tetragonal pore space structure of porous materials. The anisotropic pore space is modelled as Minkowski space, the metric tensor of which plays the fundamental role in description of transport phenomena in such a medium. To describe the metric properties of the tetragonal space, the fourth order tensor with internal symmetries of the compliance tensor used in the linear theory of elasticity of anisotropic materials has been applied. Its reduction by the automorphisms group describing point symmetries of the square net gave the general metrics of tetragonal pore space containing only two scalar parameters, that represent tortuosities of the pore space in the main and diagonal directions.